Blood lipid profiles, fatty acid deposition and expression of hepatic lipid and lipoprotein metabolism genes in laying hens fed palm oils, palm kernel oil, and soybean oil - Izuddin, Wan Ibrahim; Loh, Teck Chwen; Nayan, Nazri; Akit, Henny; Noor, Ahmadilfitri Md; Foo, Hooi Ling (Frontiers in Veterinary Science, 2023)
The palm oil, palm kernel oil and soybean oil have unique and distinctive fatty acid chain length and saturation profiles, and how they affect lipid peroxidation, fatty acid intake and metabolism is worth exploring in poultry. This study elucidated the influence the dietary oils on lipid peroxidation, blood lipid profiles, fatty acid deposition of liver, serum and yolk and the expression of liver genes related to lipid and lipoprotein metabolism in laying hens. About 150 Hisex brown laying hens were fed diets containing crude palm oil (CPO), red palm oil (RPO), refined palm oil (RBD), palm kernel oil (PKO) or soybean oil (SBO) for 16 weeks. Serum, liver and yolk lipid peroxidation were not different between dietary oils. The PKO increased liver, serum and yolk medium-chain fatty acids (MCFA). There was no difference in liver saturated fatty acids (SFA). The CPO and RPO reduced serum SFA, but the PKO increased yolk SFA. The SBO increased polyunsaturated fatty acids (PUFA) in liver serum and yolk. No difference in liver elaidic acid (C18:1-trans), but SBO lowered elaidic acid (C18:1-trans) in serum. Higher very-low density lipoprotein (VLDL) in CPO than RPO and SBO and greater serum lipase in CPO, RBD and PKO than SBO. There was no difference in sterol regulatory element-binding protein 2 (SREBP-II) between oils. Apolipoprotein VLDL-II (APOVLDL2) was upregulated in palm oils and apolipoprotein B-100 (APOB) in RBD. Downregulation in peroxisome proliferator-activated receptor-alpha (PPAR-α), peroxisome proliferator-activated receptor gamma (PPAR-γ) and low-density lipoprotein receptor (LDLR) was observed in palm oils and PKO. In conclusion, different dietary oils greatly influence several aspects of fatty acid metabolism, deposition and lipoprotein profiles but have no influence on reducing lipid peroxidation.